Adenovirus and intranuclear inclusions in appendices in intussusception. Issue 2 (February 1993) - Porter, H J; Padfield, C J; Peres, L C; Hirschowitz, L; Berry, P J
Abstract : AIMS: To examine the light and electron microscopic features of appendices removed at the time of surgical reduction of intussusception in children; and to confirm that the viral inclusions seen in some of them are due to adenovirus. METHODS: A series of 39 appendices from cases of intussusception and 15 control appendices were reviewed. Light microscopic examination of haematoxylin and eosin stained sections was performed on all of them and one appendix with large numbers of inclusions was examined by electron microscopy. Non-isotopic in situ hybridisation using a biotinylated DNA probe was carried out on sections of appendix from 30 of the cases of intussusception and from the 15 controls. RESULTS: Light microscopic examination showed viral inclusions in 19 of the appendices from the cases of intussusception and in none of the controls. Electron microscopic examination showed viral particles with the typical features of adenovirus. Most of the appendices with viral inclusions in the haematoxylin and eosin stained sections also contained adenovirus DNA as shown by in situ hybridisation. CONCLUSIONS: Viral inclusions seen in appendices from cases of intussusception are caused by adenovirus. Adenovirus DNA was not demonstrable in appendices from cases of intussusception without viral inclusions and the aetiological factors involved in intussusception in these children remain unknown.